2018
DOI: 10.1002/ejsp.2556
|View full text |Cite
|
Sign up to set email alerts
|

Power increases the self‐serving bias in the attribution of collective successes and failures

Abstract: Three studies test the effect of power on the self‐serving bias in attributing collective outcomes. The first two studies measure (Experiment 1) and manipulate (Experiment 2) power and then measure the internal (vs. external) attribution of past successes and failures. Consistently, those who feel powerful show a stronger self‐serving tendency to selectively attribute successes internally and failures externally than those who feel powerless. Experiment 3 compares the effects of power (control over others) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Multiple studies have shown that power asymmetry leads to exploitative behavior. For instance, giving individuals power increases the tendency to falsely incriminate someone for financial gain (Swanner & Beike, 2015), to make risky investments with the resources of others (Pitesa & Thau, 2013), and to take personal credit for collective accomplishments (Lammers & Burgmer, 2018).…”
Section: Power Asymmetry Leads To Exploitationmentioning
confidence: 99%
“…Multiple studies have shown that power asymmetry leads to exploitative behavior. For instance, giving individuals power increases the tendency to falsely incriminate someone for financial gain (Swanner & Beike, 2015), to make risky investments with the resources of others (Pitesa & Thau, 2013), and to take personal credit for collective accomplishments (Lammers & Burgmer, 2018).…”
Section: Power Asymmetry Leads To Exploitationmentioning
confidence: 99%
“…This hypothesis is based on the observation that people with high and low power perceive gains and losses differently. Specifically, a study by Lammers and Burgmer [ 45 ] indicated that, compared to those without power, powerful people tend to selectively attribute success internally and failures externally (i.e., showing a stronger self-serving tendency).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond decision-making, how people construe power likely also impacts their interpersonal behavior. The outcomes of power with regard to behavior toward others are manifold; for instance, power can lead to more selfish behavior-such as telling others what to do (Kipnis, 1972), attributing collective success to oneself (Lammers & Burgmer, 2019), withholding information (to protect one's power; Maner & Mead, 2010), or taking more from a common public good (but also contributing more to it under specific circumstances; De Cremer & van Dijk, 2008;Galinsky et al, 2003). We argue that such effects depend on power construal.…”
Section: Interpersonal Behavior: Construal Of Power Alters Selfishnes...mentioning
confidence: 85%